(untitled) (Journal of Ideas in Health, 2022)
Background: Anesthesia technicians work in places with a high risk of infectious diseases. Vaccination is one of the most essential methods that protect society and healthcare workers against infectious diseases. This study aims to determine anesthesia technicians’ knowledge, behavior, attitude, and vaccine hesitancy. Methods: A cross-sectional web-based study was conducted between October 2021 and February 2022 at the Ankara Yildirim Beyazit University, Turkiye. A semi-structured and self-reported online survey was recruited to collect data from the Turkish anesthesia technicians’ community. Data of 1600 participants have undergone descriptive and univariate analyses to evaluate the differences in mean scores on knowledge, attitudes, and vaccine hesitancy. Results: The mean age of respondents was 24 years (±6.15). More than two-thirds (79.2%) were females, single (84.9%), aged less than 30 years (88.4%), and unemployed (61.1%); however, 12.4% had chronic diseases. The mean knowledge, attitude, and vaccine hesitancy score were 13.24± 3.22 (range: 0-21), 11.19 ± 3.19 (range: 0-15), and 28.67± 6.64, range: 12–60), respectively. Most respondents had information (1458, 91.1%) about COVID-19 vaccines, and 1247(77.9%) had been vaccinated. However, 240 (16.3%) did not receive vaccines at all compared to 59 (3.7%) who completed the thirteen recommended vaccines in Turkiye. The mean of vaccine hesitancy was significantly higher among females (P=0.001), unemployed (P=0.007), residents in Southeast Anatolia (P=0.001), and those who did not use medication continuously (P=0.016). However, participants aged 40 years and above (P=0.013) showed the lowest mean of vaccine hesitancy than the other age groups. Conclusion: Appropriate training and guidance might increase the vaccination information and enhance the vaccination rates among anesthesia technicians.